2018
DOI: 10.25077/jka.v6.i3.p696-701.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ekstrak Kelopak Rosella Merah (Hibiscus sabdariffa Linn.) Mampu Memperbaiki Histopatologi Hepar Tikus Wistar yang Diberi Paparan Asap Rokok

Abstract: Abstrak Prevalensi penduduk di Indonesia usia merupakan salah satu sumber radikal bebas. rosella merah terhadap degenerasi hepatosit tikus dan dibagi menjadi empat kelompok rosella merah dosis 270 mg/bw, kontrol positif dan kontrol negatif. Kelompok per rosella dipagi hari dan setelah itu dipapar 2 rokok per hari. Kontrol positif diberi pakan standar + dipapar 2 rokok per hari. Kontrol negatif hanya diberi pakan standar. Penelitian gambaran histopatologi hepar. Pemberian ekstrak kelopak rosella merah dosis 270… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several studies have shown that roselle effectively lowers blood pressure, lowers fat profile, has antiinflammatory, antimicrobial, anti-anaemia, anticarcinogenic, hepatoprotective, and improves fertility disorder (Riaz and Chopra, 2018). Another study showed that roselle extract prevented the increase in MDA (Ulilalbab et al, 2015); thus preventing and improving rat hepatocyte degeneration in rats exposed to cigarette smoke (Ulilalbab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that roselle effectively lowers blood pressure, lowers fat profile, has antiinflammatory, antimicrobial, anti-anaemia, anticarcinogenic, hepatoprotective, and improves fertility disorder (Riaz and Chopra, 2018). Another study showed that roselle extract prevented the increase in MDA (Ulilalbab et al, 2015); thus preventing and improving rat hepatocyte degeneration in rats exposed to cigarette smoke (Ulilalbab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%